Glycogen Dynamics Drives Lipid Droplet Biogenesis during Brown Adipocyte Differentiation - Mayeuf-Louchart, Alicia (Cell Rep, 2019)
Browning induction or transplantation of brown adipose tissue (BAT) or brown/beige adipocytes derived from progenitor or induced pluripotent stem cells (iPSCs) can represent a powerful strategy to treat metabolic diseases. However, our poor understanding of the mechanisms that govern the differentiation and activation of brown adipocytes limits the development of such therapy. Various genetic factors controlling the differentiation of brown adipocytes have been identified, although most studies have been performed using in vitro cultured pre-adipocytes. We investigate here the differentiation of brown adipocytes from adipose progenitors in the mouse embryo. We demonstrate that the formation of multiple lipid droplets (LDs) is initiated within clusters of glycogen, which is degraded through glycophagy to provide the metabolic substrates essential for de novo lipogenesis and LD formation. Therefore, this study uncovers the role of glycogen in the generation of LDs.